Matrix Metalloproteinases in Health and Disease - Serra, Raffaele (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Matrix metalloproteinases (MMPs) are members of an enzyme family and are critical for maintaining tissue allostasis. MMPs can catalyze normal turnover of the extracellular matrix (ECM) together with other metalloproteinases such as ADAM (a disintegrin and metalloproteinase) and ADAMTS (a disintegrin and metalloproteinase with thrombospondin motif) families. MMP activity is also regulated by a group of endogenous proteins called tissue inhibitor of metalloproteinases (TIMPs). All these proteins have a pivotal role involving ECM remodelling in normal physiological processes such as wound healing, embryogenesis, angiogenesis, bone remodelling, immunity, and the female reproductive cycle. An imbalance in the expression or activity of MMPs can also have important consequences in diseases such as cancer, cardiovascular disease, peripheral vascular disease, chronic leg ulcers, and multiple sclerosis. In recent years, MMPs have been found to play an important role in the field of precision medicine, as they may serve as biomarkers that may predict an individual's disease predisposition, state, or progression. MMPs are also thought to be a sensible target for molecular therapy. The aim of this Special Issue is to explore the most recent findings in this field that may have an impact in healthcare systems.